Effect of Rabbit Production Factors on Revenue of Rabbit Farmers in Berastagi District, Karo Regency - Muhammad Bayu; Sayed Umar; Hasnudi .; Nurzainah Ginting; Yusuf Leonard Henuk (Jurnal Peternakan Integratif, 2019)
The aim of this research was to investigate the influence of rabbitproduction factors on rabbit farmers income in the District of Berastagi Regency ofKaro which include Litter Size, Sum of Wean, Sum of Deaths, Feed Cost and Sum ofLabor; and knowing rabbit business in District of Berastagi Regency of Karo isdeserves to be forwarded. The research method used census method done twice for twomonths to take as many as 48 respondent farmers. Factor analysis was obtained byregression analysis while business feasibility obtained by Revenue Cost Ratio (RatioR/C), Benefit Cost Ratio (Rasio B/C) and Break Event Point (BEP) analysis. Theresults showed that the factor affect rabbit farmers income were Sum of Deaths andSum of Labor. Financial analysis of rabbit farmers were R/C=5,61, B/C=4,24, PriceBEP=Rp 9.875 dan Production BEP=22 pieces. It conclude that the factor affect rabbitfarmers income were Sum of Death and Sum of Labor. Rabbit business is profitableand feasible to conduct.